Kaznodzieja jako autor homilii. Aspekty homiletyczno-prawne - Broński, Włodzimierz (Studia Pastoralne, 2026)
Prophet of the Highest, Christ`s witness, competent word of God servant – these terms are used to define the preacher in literature. However, homily is understood as the word of God inside preacher`s humane word. From the theological point of view it is the result of specific but also individual preacher`s composition. In present essay, after introduction theological basis of preacher`s mission, homily issues were discussed as the result of creative work and also selected legal aspects related to the homily authorship were mentioned.